2011
DOI: 10.1002/ps.2114
|View full text |Cite
|
Sign up to set email alerts
|

Spray drift as influenced by meteorological and technical factors

Abstract: Under specified conditions, the present results indicate a simple relation between the total spray drift and volume fractions of droplets ≤ 100 µm. Given the nozzle type, it was concluded that the most decisive factors determining TSD are wind speed and boom height. Evaluating the relative importance of the meteorological and technical factors contributes to increasing knowledge in this field of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 7 publications
5
89
0
12
Order By: Relevance
“…This is in agreement with other studies that showed that the measurements of the fall-out drift can, in some cases, differ by as much as a factor of 10 for the same nozzle size and working pressure both for air blast sprayers (Zande et al, 2012) and for boom (Arvidsson et al, 2011). This difference could be attributed to weather conditions, spray application technology, and different measurement procedures (Nuyttens et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with other studies that showed that the measurements of the fall-out drift can, in some cases, differ by as much as a factor of 10 for the same nozzle size and working pressure both for air blast sprayers (Zande et al, 2012) and for boom (Arvidsson et al, 2011). This difference could be attributed to weather conditions, spray application technology, and different measurement procedures (Nuyttens et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have evaluated and quantified the effect of the different variables that strongly influenced spray drift; these factors may be categorised as follows: equipment and application techniques, spray characteristics, operator care and skill (Arvidsson et al, 2011), and environmental and meteorological conditions. Nevertheless, classifying spray techniques is challenging because these vary greatly due to the influence of environmental conditions and crop growth and leaf canopy status of different bush and tree crop types (Ozkan & Zhu, 1998;Zande et al, 2000Zande et al, , 2010Balsari et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More often practically used is especially VMD average, which is a critical indicator of the biological efficiency of a treatment. Because VMD makes provision for the dimension of droplets, it characterizes more precisely the quality and suitability of a droplet spectrum for each applied liquid.To sum up, we can say that VMD correlates positively with the size of a nozzle, while it correlates negatively with the discharge angle (ARVIDSSON 1997). KOVAŘÍČEK (1997) agrees with this predication and suggests three general principles of the relation between the size of droplets and nozzles: 1.…”
mentioning
confidence: 58%
“…To sum up, we can say that VMD correlates positively with the size of a nozzle, while it correlates negatively with the discharge angle (ARVIDSSON 1997). KOVAŘÍČEK (1997) agrees with this predication and suggests three general principles of the relation between the size of droplets and nozzles: 1.…”
mentioning
confidence: 58%
“…In brief, these variations whilst performing were low. Notwithstanding, this information is important since, among all factors interfering with pesticide drifting, environmental and weather conditions (temperature, air humidity and wind speed) are the most impacting (ARVIDSSON, 2011;HILZ & VERMEER, 2013;GIL et al, 2014). Figure 1 displays a graphic of drift index up to 320 m far from target area.…”
Section: Resultsmentioning
confidence: 99%